Cerebral Microbleeds May Be Less Detectable by Susceptibility Weighted Imaging MRI From 24 to 72 Hours After Traumatic Brain Injury - Környei, Bálint S.; Szabó, Viktor; Perlaki, Gábor; Balogh, Bendegúz; Szabó Steigerwald, Dorottya K.; Nagy, Szilvia A.; Tóth, Luca; Büki, András; Dóczi, Tamás; Bogner, Péter; Schwarcz, Attila; Tóth, Arnold (Frontiers in Neuroscience, 2021)
Purpose - A former rodent study showed that cerebral traumatic microbleeds (TMBs) may temporarily become invisible shortly after injury when detected by susceptibility weighted imaging (SWI). The present study aims to validate this phenomenon in human SWI. Methods - In this retrospective study, 46 traumatic brain injury (TBI) patients in various forms of severity were included and willingly complied to our strict selection criteria. Clinical parameters potentially affecting TMB count, Rotterdam and Marshall CT score, Mayo Clinic Classification, contusion number and total volume were registered. The precise time between trauma and MRI (5h 19 min - 141h 54 min, including SWI and FLAIR) were individually recorded, TMB and FLAIR lesion counts were assessed. Four groups were created based on elapsed time between the trauma and MRI: 0-24h, 24-48h; 48-72h and >72h. Kruskal Wallis, ANOVA, chi square and Fisher exact tests were used to reveal differences among the groups within clinical and imaging parameters, statistical power was calculated retrospectively for each comparison. Results- Kruskal-Wallis ANOVA with Conover post-hoc analysis showed significant (p=0.01; 1->0.9) median TMB number differences in the subacute period: 0-24h=4.00 (n=11); 24-48h=1 (n=14); 48-72h=1 (n=11); 72h< =7.5 (n=10). Neither clinical parameters nor FLAIR lesions depicted significant differences among the groups. Conclusion- Our results demonstrate that TMBs on SWI MRI may temporarily become less detectable at 24-72 hours following TBI.